Availability of trace minerals in feed ingredients and supplemental sources (inorganic, organic, and nano) in broiler chickens - Junhyung Lee; Minju Kim (Journal of Animal Science and Technology)
This trial aimed to investigate the bioavailability of copper, iron, zinc, manganese, and selenium in nano, organic, and common inorganic forms. At d 15 of age, a total of 480 birds, one-day-old Ross 308 males, were used in the current trial and housed in metabolic cages for chickens. All birds were randomly arranged according to their body weight (436 ± 23 g) and allotted to 8 experimental diets in a completely randomized design. There were 12 replicates in each diet group with 5 birds per replicate. The experimental diets consisted of 7 diets, containing corn, soybean meal (SBM), corn gluten meal (CGM), fish meal, inorganic premix, organic premix, and nano-premix. There was a higher apparent ileal digestibility (AID) and standardized ileal digestibility (SID) of copper in corn compared with SBM, CGM, and fish meal (p < 0.01). An increase in AID of iron was observed in broiler chickens fed corn and fish meal, however, the highest SID of iron was observed in chickens fed fish meal (p < 0.01). Moreover, the SID of iron was higher in chickens fed corn compared with SBM and CGM. The AID and SID of zinc in CGM treatment were higher than the SBM. An increase in AID of manganese was observed in broiler chickens fed fish meal compared with the CGM and SBM, however, the highest SID of manganese was observed in chickens fed CGM (p < 0.01). There was the highest AID and SID of selenium in chickens fed fish meal compared with SBM, CGM, and fish meal (p < 0.01). Moreover, the SID of selenium was higher in chickens fed CGM compared with SBM and corn. The AID and SID of copper, iron, zinc, manganese, and selenium were higher (p < 0.01) in the nano- and organic forms compared with the inorganic form. In conclusion, fish meal showed a higher bioavailability of iron, manganese, and selenium compared with CGM and SBM. Moreover, the nano-minerals showed a similar bioavailability compared with the organic form.